Experiences of a One-hour Algorithm in Chest Pain Patients With a Nonelevated Troponin T at Presentation. Issue 1 (March 2018) - Pettersson, Anna; Ljung, Lina; Johansson, Caroline; Heilborn, Umut; Jernberg, Tomas; Frick, Mats; Eggers, Kai M.; Lindahl, Bertil; Linder, Rikard; Martinsson, Arne; Svensson, Per
Abstract : Background: We aimed to evaluate the use of a 1-hour measurement of high-sensitivity cardiac troponin T (hs-cTnT) in an emergency department (ED) population of chest pain patients with a nonelevated baseline hs-cTnT and to examine the prevalence of early dynamic changes in hs-cTnT and the association with admission rate, diagnosis, and outcome. Methods: All patients with a chief complaint of chest pain presenting to the ED of Karolinska University Hospital, Solna, Sweden, from December 2014 to September 2015 who had a baseline hs-cTnT of ⩽14 ng/L and a second value obtained within >30 to ⩽90 minutes were followed for 30 days regarding admission, readmission, myocardial infarction (MI), and death. Results: A total of 1091 patients were included. Dynamic 1-hour changes in hs-cTnT defined as an increase or decrease of ≥3 ng/L occurred in 23 patients (2.1%). Fifteen patients (65.2%) in the dynamic group were admitted, compared with 148 patients (13.9%) in the nondynamic group ( P < 0.001). Four of the admitted patients (26.7%) in the dynamic and 1 (0.7%) in the nondynamic group were diagnosed with an MI ( P < 0.001). No death or MI occurred within 30 days among those discharged from the ED. Conclusions: Dynamic 1-hour changes in hs-cTnT were uncommon but associated with a higher rate of admission and of MI in an unselected population of chest pain patients with a nonelevated hs-cTnT at presentation. Lack of dynamic changes makes MI highly unlikely, and a 1-hour measurement may facilitate an early rule out of MI but should be used together with clinical assessment. Abstract : Supplemental Digital Content is available in the text.